Порівняльні показники роботи сошників двох типів - Сало, В. М.; Лещенко, С. М.; Вовнянко, Б. Г.; Мороз, С. М.; Salo, V.; Leshchenko, S.; Vovnianko, B.; Moroz, S. (ЦНТУ, 2024)
В статті розглянуті особливості забезпечення якісних показників виконання технологічного процесу сівби сільськогосподарських культур з використанням сошників різних типів. Представлена методика проведення польових порівняльних випробувань сошників з гострим кутом входження в ґрунт, які представлені експериментальною посівною секцією та серійним дводисковим сошником з прикочуючим котком. До складу секції входить сошник з гострим кутом входження в ґрунт, обладнаний утримуючою п’яткою. The article considers specific features of ensuring quality indicators of the technological process of sowing crops using coulters of various types. The existing designs of coulters are analysed, indicating their advantages and disadvantages. It is emphasised that the use of disc coulters for direct sowing is limited due to the need to apply significant efforts to deepen them into the soil. A well-known alternative design of operating parts for seed placement into the soil is a coulter with a sharp angle of entry, but its design and parameters need further improvement.The paper proposes the design of a sowing section for sowing spiked grain crops on the soil after no till tillage methods with the presence of plant residues in the upper soil layers. The basis of this sowing section is a coulter with a sharp angle of entry into the soil, the design of which provides the use of a holding heel.
Comparative Performance of Two Types of Coulter
Keywords: сівба; сошник; насіння; глибина загортання; якість процесу; сошник з гострим кутом входження в ґрунт; дисковий сошник; sowing; coulter; seed; sowing depth; process quality; coulter with a sharp angle of entry into the soil; disc coulter